2002
DOI: 10.1016/s0014-5793(02)03590-1
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of IKK‐γ oligomerization by the human T‐cell leukemia virus oncoprotein Tax

Abstract: Human T-cell leukemia virus type 1 oncoprotein Tax activates NF-U UB through direct binding to IKK-Q Q, the regulatory component of the IU UB kinase complex. Mechanisms by which IKK-Q Q adapts the Tax signal to the IU UB kinase are poorly understood. Here we demonstrate that IKK-Q Q forms homodimer and homotrimer both in vitro and in yeast or mammalian cells through a C-terminal domain comprising amino acids 251419. In contrast, Tax protein targets a central region of IKK-Q Q, which consists of amino acids 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 45 publications
4
31
0
Order By: Relevance
“…These results reduce the size of the minimal oligomerization domain to 87 residues (amino acids 251-337). Our observation that fulllength NEMO (1) and either CC2-LZ or the isolated CC2 subdomain (this report) all form trimeric oligomers is in agreement with other studies (7,20). Tegethoff et al (21) proposed that the minimal oligomerization domain has a tetrameric structure.…”
Section: Role Of C-terminal Subdomains In Nemo Oligomerization-supporting
confidence: 93%
See 2 more Smart Citations
“…These results reduce the size of the minimal oligomerization domain to 87 residues (amino acids 251-337). Our observation that fulllength NEMO (1) and either CC2-LZ or the isolated CC2 subdomain (this report) all form trimeric oligomers is in agreement with other studies (7,20). Tegethoff et al (21) proposed that the minimal oligomerization domain has a tetrameric structure.…”
Section: Role Of C-terminal Subdomains In Nemo Oligomerization-supporting
confidence: 93%
“…In vitro cross-linking experiments with the non-cleavable amine-reactive bis(sulfosuccinimidyl)suberate cross-linker established that pure recombinant NEMO autoassociates in dimers and trimers (20). Using a very similar amine-reactive cross-linking agent, ethylene glycol-bissuccinimidylsuccinate, Rothwarf et al (7) also found dimeric and trimeric forms of recombinant NEMO.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Forced oligomerization of IKK␥ by fusion with the FKBP12 polypeptide leads to NF-B activation and the redistribution of the IKK subunits from uniform to punctate cytoplasmic staining (32). Tax also promotes the oligomerization of IKK␥ through a direct interaction (33). Thus, Tax likely triggers the oligomerization of IKK␥, through an undefined mechanism, leading to the oligomerization of associated IKKs and the redistribution to the perinuclear hot spots discovered in the present study.…”
Section: Discussionsupporting
confidence: 56%
“…52 In fact, LRR, which contains three leucine residues repeated after each seven residues, does not bind directly with IKK-g, but it favors the homodimerization of Tax, which in turn induces IKK-g oligomerization and consequently, the catalytic activity of IKK. 52,53 In addition, Tax can constitutively activate IKK, by interacting with some upstream kinases such as MEKK1. 54 NIK also seems to play an important role in the IKK activation by Tax, since negative-dominant mutants of NIK inhibit NF-kB activation by Tax.…”
Section: Overview On Nf-jbmentioning
confidence: 99%